BILATERAL OSTEOPOROTIC FEMUR FRACTURES IN A YOUNG WOMAN: AN AFTERMATH OF EMPTY SELLAR SYNDROME - Iberahim, Nor Afifah; Kannesan, Dineash Kumar; Yahaya, Nor Hayati; Borhan, Marisa Khatijah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Empty sella syndrome (ESS) is characterized by the radiological finding of a flattened pituitary gland within the empty sella turcica due to subarachnoid space expansion, commonly associated with hormonal deficiencies. We report a rare case of panhypopituitarism due to primary ESS in a young female who presented with bilateral osteoporotic femur fractures. CASE A 38-year-old aboriginal female was first brought to the orthopedic team for persistent right hip pain and a limping gait for several years. There was no prior history of trauma, surgery or irradiation. CT of bilateral hip joints showed generalized osteopenia with non-union bilateral femur fracture. Bone mineral density revealed osteoporosis of the lumbar spine and left radius with Z-score of -4.3 and -6.6, respectively. Further evaluation for secondary osteoporosis revealed short stature with a low BMI of 17 kg/m2. Notably, she has primary amenorrhea and delayed puberty, with Tanner stage 1 breast and pubic hair development. Family history was unremarkable except for one younger sister with short stature. Anterior pituitary hormone profile revealed central hypothyroidism (TSH: 2.05 mIU/L, fT4: 6.7 pmol/L), hypogonadotrophic hypogonadism (serum estradiol <55.1 pmol/L, FSH: 0.3 IU/L, LH <0.2 IU/L), low prolactin (35.7 mIU/L) and low IGF-1 level of 11.9 ng/ml (69 -227 ng/ml) suggestive of growth hormone deficiency. Additionally, her vitamin D level was insufficient, 68.79 nmol/L. Short Synacthen test revealed adequate cortisol response. MRI of pituitary reported features of empty sella, confirming the diagnosis of primary ESS. She received hormonal replacement therapy, including estradiol, for pubertal induction. She was counselled for right total hip replacement, but she was not keen. CONCLUSION Panhypopituitarism observed in ESS affects bone remodeling, leading to early osteoporotic fracture. Treatment with hormonal replacement is essential to restore secondary sexual characteristics for psychosocial well-being as well as to improve bone health to reduce the risk of further fracture.